PERKINS INTERNATIONAL ACADEMY: EDUCATION OF LEARNERS WITH MULTIPLE DISABILITIES AND DEAFBLINDNESS (Proceedings of International Conference on Special Education, 2017)
This presentation will address the worldwide challenges in assuring that children with multiple disabilities and deafblindness have access to quality educational services. It will look at the mandate put forth to countries worldwide to meet the United Nations Sustainable Development Goals, focusing on the implications of Goal 4. Every student with multiple disabilities and vision impairment (MDVI) presents a unique educational challenge. Teachers need specialized training and skills to understand the needs of the students and adaptations to enhance their learning. Perkins International has consolidated 95 years of global teacher training expertise into its first Perkins International Academy courses. This professional training program aims to improve the lives of children who are visually impaired with multiple disabilities by training their teachers and related professionals on the best educational practices. The Perkins International Academy is based upon a set of standard teacher competencies for teachers of learners who are visually impaired with multiple disabilities. This population includes children with visual impairment and additional disabilities- including intellectual disabilities, physical disabilities, hearing impairment, cerebral palsy, autism, behavioural challenges, complex health challenges and those with deafblindness. These children are among the most vulnerable in the world. There are currently two courses available through Perkins International Academy: Education of Learners with Multiple Disabilities and Deafblindness-Foundations Level Education of Learners with Multiple Disabilities and Deafblindness-Advanced Level The presenter will describe Perkins International Academy, a model that Perkins International is using to successfully meet the challenge of building a highly qualified workforce to serve this population of children and young adults throughout a variety of educational and care settings. The description of the Perkins International Academy will be put into the context of the overarching program of any country’s development efforts to assure sustainable systems of services for students with multiple disabilities